Hepatorenal Syndrome: Diagnosis and Treatment - newsreel - - Enescu Aurelia; Petrescu F.; Mitruţ P.; Petrescu Ileana Octavia; Pădureanu V.; Enescu Anca Ştefania (Sciendo, 2016)
Hepatorenal syndrome (HRS) is defined as renal failure that occurs in the presence of severe acute or chronic liver disease in the absence of underlying renal pathology. Due to the functional nature of the disease and the absence of specific diagnostic markers, HRS diagnosis is determined based on positive criteria associated with excluding other causes of renal failure in patients with liver cirrhosis and ascites. Differentiation from other types of acute or chronic renal disease is extremely difficult and therapeutic options are limited, prophylactic behavior is most appropriate in patients with severe hepatic disease and risk factors for the installation of hepatorenal syndrome.